2006
DOI: 10.1007/s00244-005-2094-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in Poultry Feed in Kuwait

Abstract: A survey was conducted at a poultry feed production unit in Kuwait for mycotoxin contamination in the samples of yellow maize, soybean meal, wheat bran used as raw material and the poultry feed prepared for broiler starter, broiler finisher, and layer mash. Individual aflatoxins were determined by high-pressure liquid chromatography after immunoaffinity column purification. Repeated analysis revealed average aflatoxin concentration in maize at 0.27 ppb (range 0 to 1.69 ppb), soybean meal at 0.20 ppb (range 0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 33 publications
1
44
0
1
Order By: Relevance
“…Pussemier et al 29 found OTA in 40% of wheat grain samples analysed, with levels ranging from 0.04 to 1.10 µg kg −1 . 42 Beg et al 43 sampled raw materials and poultry feeds from a single poultry feed producer and found average OTA levels of 4.6 and 9.6 µg kg −1 respectively, with contamination rates ranging from 71.4 to 100%. In Turkey, 115 feedstuffs and 84 complete feeds collected from different regions showed OTA contamination rates of 47.8% (1.10-874 µg kg −1 ) for feedstuff samples, 27.3% (4.90-24.3 µg kg −1 ) for poultry feeds and 80.7% (1.10-975 µg kg −1 ) for ruminant feeds.…”
Section: Discussionmentioning
confidence: 98%
“…Pussemier et al 29 found OTA in 40% of wheat grain samples analysed, with levels ranging from 0.04 to 1.10 µg kg −1 . 42 Beg et al 43 sampled raw materials and poultry feeds from a single poultry feed producer and found average OTA levels of 4.6 and 9.6 µg kg −1 respectively, with contamination rates ranging from 71.4 to 100%. In Turkey, 115 feedstuffs and 84 complete feeds collected from different regions showed OTA contamination rates of 47.8% (1.10-874 µg kg −1 ) for feedstuff samples, 27.3% (4.90-24.3 µg kg −1 ) for poultry feeds and 80.7% (1.10-975 µg kg −1 ) for ruminant feeds.…”
Section: Discussionmentioning
confidence: 98%
“…Fungal growth cause direct losses in volume and quality of feed ingredients leaving behind some poisonous mycotoxins, which contaminate feed raw materials and finished feeds. Poultry are highly susceptible to mycotoxicoses caused by aflatoxins, trichothecenes, ochratoxin, and fusariotoxins (Beg et al, ; Didwania & Joshi, ; Mabbett, ). Most mycotoxicoses of poultry are caused by an intake of low concentration of contaminants over a long period of time with typical chronic symptoms of poor growth and feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…An HPLC system (Waters 600E System Controller) with a fluorescence detector (Waters 470) was used for aflatoxins quantification. A reversed phase LC-18 column (Novapak) was used with a mobile phase consisting of a mixture of acetonitrile-water-acetic acid (18:82:1, v/v/v) at a flow rate of 1 ml min -1 and fluorescence detection: ex 365 nm, em 440 nm (Beg et al 2006;Alam et al 2012). …”
Section: Extraction and Analysis Of Aflatoxinsmentioning
confidence: 99%
“…The main ingredients include corn grains, rice polishing, cotton seed meal, rape seed meal, corn gluten, soybean meal, fish meal, vitamin premix and vegetable oils (Nadeem et al 2005;Raza et al 2009). As a rich source of starches, broiler finisher feed is often fraught with fungal contamination and aflatoxin production (Khan 1994;Beg et al 2006;Zinedine et al 2007). Moreover, warm moist tropical climates, long post-harvest periods and storage structure also favour mould growth and production of aflatoxins (Ilangantileke 1987;Hell et al 2000;Klich 2007).…”
Section: Introductionmentioning
confidence: 99%